The effect of facilitated tucking and white noise on stress and sleep of newborns receiving nasal continuous positive airway pressure - Dag, Yeliz Suna; Yayan, Emriye Hilal (Elsevier Science Inc, 2024)
Objective: To investigate the effects of facilitated tucking and white noise on stress and sleep in neonates receiving nasal continuous positive airway pressure (CPAP). Method: This study was conducted as a randomised controlled experimental study of neonates receiving nasal CPAP in neonatal intensive care units. The study sample consisted of 108 newborns (facilitated tucking (n = 36), white noise (n = 36) and control (n = 36)) receiving nasal CPAP support in the NICU. The neonates' sleep parameters were recorded by actigraphy for 24 h. Data were collected using the Neonatal Descriptive Information Form, the Sleep Tracking Form and the Neonatal Stress Scale. Percentage, mean, chi -squared and one-way ANOVA were used for data analysis. Results: It was found that 50.9% of the newborns were female, their mean gestational age was 33.54 +/- 3.38, their mean height was 43.56 +/- 5.12, and their mean weight was 2139.23 +/- 827.82. The total sleep time of the neonates in the facilitated tucking and white noise group increased by 3 h, their sleep efficiency increased by 20% and their mean stress scores decreased ( p < 0.05). Conclusion: Facilitated tucking and white noise each showed a similar improvement in sleep duration and sleep efficiency and a reduction in stress scores in neonates receiving nasal CPAP. Close monitoring of sleep in this population and supportive care practices are recommended. Practice implications: The findings of this study may help to reduce sleep problems and stress levels in the clinical care of neonates in the NICU through developmental nursing practices. (c) 2024 Elsevier Inc. All rights reserved.
Keywords: White noise; Facilitated tucking; Stress; Sleep; Neonates